Formation of Residential Constructions of Early Nomads (Journal of history, 2019)
The article deals with one of the most important issues of historical ethnography of the Kazakh people, such as the study of the genesis of residential buildings of the early nomads. This problem needs to be studied comparatively, and not only on the basis of a specific region, but also on a large scale, in addition to the neighboring peoples. The culture of the peoples of Northern and Central Asia can lead to a wider picture of the problem, establishing closer relations with each other. The problem here is the analysis of the genesis of the yurt, which is the main dwelling for nomads.The yurt is home to many nomadic tribes living in the steppes of Eurasia. Of these, such ancient tribes of the sako-gunian times, the ancient turkic and mongolian tribes, the persian-speaking djemshids and the khazars.